Peran Guru PAI dalam Membangun Karakter Mandiri Siswa Kelas X di MA Darul Ulum Pasinan Baureno Bojonegoro - Zahrotul Firdaus; Khotimah Suryani; Mahbub Junaidi (AJER: Advanced Journal of Education and Religion, 2025)
This study aims to assess the role of Islamic religious education teachers (PAI) in building independent characters of class X students at the Ma Darul Ulum Pasinan Baureno Bojonegoro. Independence is one of the important characters that students must have to face future challenges. PAI teachers have a strategic role in instilling independence values through religious teaching and daily behaviors. The research method used is a qualitative method with a case study approach. Data is collected through observation, interview, and documentation. The results of this study indicate that PAI teachers at Ma Darul Ulum Pasinan Baureno Bojonegoro have carried out various efforts to build students' independent characters. Pai teachers provide individual tasks that encourage students to learn independently, facilitate group discussions to improve the ability to communicate and work, and provide sustainable guidance and motivation. Although most students show good independence, there are several groups that still need to increase teamwork. This can be seen from several groups whose members work alone, there is no clear division of tasks, and the lack of interaction between members. Therefore, more intensive and sustainable guidance from teachers is very necessary to optimize student learning independence. This study concluded that the role of pie teachers was very important in shaping the character of the students, but the need for a more effective strategy to overcome the constraints in teamwork.